L’intelligence des images - l’intericonicité, enjeux et méthodes - Mathilde ARRIVÉ (E-REA)
This theoretical introduction addresses graphic transfers as symbolic and cultural operations, through the prism of intericonicity and within the wider framework of an anthropology of images. First, this article seeks to offer some definitional landmarks and to trace the intellectual genealogy of the notion in order to situate it within the existing academic landscape, identify its specificity, compare it with associated or competing notions, and assess its limits, productivity and relevance in relation to new visual objects. The article then moves on to tackle the various symbolic, social and political stakes raised by intericonicity, aiming at mapping out new possible areas of inquiry.